Hvorfor benchmarker kommunerne? - Brødsgaard, Marie-Louise Frølich; Gjørling, Mathias (Politik, 2015)
In the municipal sector, the use of benchmarking is widely promoted but little is known as to the e ects of the use. us, why do the six biggest municipal cities in Denmark partake in a voluntary cooperation to develop key performance indicators? Seeking the answer in the municipalities’ own reasoning, we analyze the intentions with the cooperation and the observable e ects. Our analysis shows that the intention with the cooperation is a use that leads to changes in results, e.g. improved cost e ectiveness, but that the actual e ects are limited to the organizational actions speech and decisions. is inconsistency between intentions and the observable e ects begs the question: why do the six municipalities continue to benchmark? We conclude that the municipalities partake in the cooperation because politicians and senior administration o cials demand the continuous production of the reports due to both a logic of consequentiality and a logic of appropriateness.